Chlorella vulgaris functional alcoholic beverage: Effect on propagation of cortical spreading depression and functional properties. - Danielli M M Dantas (Public Library of Science (PLoS), 2021)
Recent advances in microalgae biotechnology have proven that these microorganisms contain a number of bioactive molecules, that can be used as food additives that help prevent disease. The green microalga Chlorella vulgaris presents several biomolecules, such as lutein and astaxanthin, with antioxidant capacity, which can play a protective role in tissues. In this study, we produced and analyzed a C. vulgaris functional alcoholic beverage (produced using a traditional Brazilian alcoholic beverage, cachaça, and C. vulgaris biomass). Assays were conducted in vitro by radical scavenging tests, and in vivo, by modeling cortical spreading depression in rat brains. Scavenging radical assays showed that consumption of the C. vulgaris alcoholic beverage had a DPPH inhibition of 77.2%. This functional alcoholic beverage at a concentration of 12.5 g L-1 significantly improved cortical spreading depression velocity in the rat brains (2.89 mm min-1), when compared with cachaça alone (3.68 mm min-1) and control (distilled water; 3.25 mm min-1). Moreover, animals that consumed the functional beverage gained less weight than those that consumed just alcohol and the control groups. These findings suggest that the C. vulgaris functional alcoholic beverage plays a protective physiologic role in protecting brain cells from the effects of drinking ethanol.